Unwarranted wage changes and the return on capital - Margarita Katsimi; Sarantis Kalyvitis; Thomas Moutos (Center for Economic Studies and ifo Institute (CESifo), 2009)
Casual empiricism suggests that unwarranted wage changes, defined as the part of wage growth that is not explained by changes in labour productivity, are negatively associated with the return on capital. The main point of this paper is to show that unwarranted wage changes have no causal effect on capital return. To this end, we show that standard theoretical models, in which unwarranted wages changes and the return on capital are endogenously determined, do not necessarily predict a negative association between them. We then estimate aggregate net return on capital equations using panel data for 19 OECD countries for the period 1970-2000 in which we account for the endogeneity of unwarranted wage changes by exploiting variations in institutional and labour market characteristics. We find that unwarranted wage changes do not affect the return on capital. This result remains robust to alternative empirical specifications and to alternative definitions of profitability and unwarranted wage changes. An implication of our findings is that standard calls for reforms aiming at wage moderation following the appearance of unwarranted wage changes are not always justified.
Keywords: E24; E25; 330; capital return; profits; unwarranted wages; productivity; endogeneity; Lohnpolitik; Lohnniveau; Arbeitsproduktivität; Kapitalertrag; Gewinn; Arbeitsmarktflexibilisierung; Schätzung; OECD-Staaten